If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 6y = 0 Solving 12x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 12x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 12x + 0 = 0 + -6y 12x = 0 + -6y Remove the zero: 12x = -6y Divide each side by '12'. x = -0.5y Simplifying x = -0.5y
| 2(-6p+7)+4(p+3)= | | 3x^2-20x+25= | | 11d-4d-3d+d-4d=12 | | 23-4r=3 | | -48-3x=42+2x | | 6X9-/5X | | (14-2x)+40= | | 3(6+t)-1= | | 3(-5x-4)-2x=6 | | 3a^2+4a-7= | | 5x+2(6x-18)=117 | | 5m+-2-7m=20 | | 4=36/m | | 3a-5=5+a | | -6=14n | | 18x-4(3x+4)=(9x-5)-5(3x+7) | | 15xy-30y= | | 3d-2d-d+2d=8 | | F=1/2kw | | 3s-42=33 | | 6(c+2)=5(1-3c) | | 1x/5=14 | | 6[x+2]=60 | | 10d-7d=9 | | -x^3+3x+1.5=0 | | 4(1-7n)-5= | | d/7+75=81 | | -x^3+3x-1.5=0 | | 3(x-4)-2=5x | | 0.2(15y+2)=0.5(8y-3) | | 3x(x+17)=0 | | 1/2(3x=6)=3(x-2) |